2023
DOI: 10.3390/jcm12134490
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Weight Management: The Role of Leptin—A Systematic Review and Update of Clinical Data from 2000–2022

Abstract: A well-balanced metabolism means a lower risk for metabolism-related neuropsychiatric disorders. Leptin is a secretory adipokine involved in the central control of appetite that appears to play a role in the etiology of feeding-related disorders. Additionally, the influence of exercise on feeding behaviors potentially modulates the circulation of metabolites that signal through the central nervous system. In this systematic review, we collected the recent clinical evidence on the effect of exercise on leptin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 90 publications
0
6
0
1
Order By: Relevance
“…Hypoleptinemia seems to be due to food restriction per sé, further designating leptin as a critical marker of starvation. The effect of physical activity in reducing leptin levels in EXE rats is due to its role in stabilizing appetite in a condition of exercise-induced negative energy imbalance, thus suggesting that its reduction, despite of a lesser extent than that observed in ABA rats, might be associated with the increased metabolic demands imposed by exercise to regulate energy homeostasis [ 64 ]. We observed that EXE and FR rats restored the amount of circulating leptin back to CTRL levels following the 7-day recovery period, suggesting its ability to physiologically respond to food consumption and to the normalization of bodyweight.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoleptinemia seems to be due to food restriction per sé, further designating leptin as a critical marker of starvation. The effect of physical activity in reducing leptin levels in EXE rats is due to its role in stabilizing appetite in a condition of exercise-induced negative energy imbalance, thus suggesting that its reduction, despite of a lesser extent than that observed in ABA rats, might be associated with the increased metabolic demands imposed by exercise to regulate energy homeostasis [ 64 ]. We observed that EXE and FR rats restored the amount of circulating leptin back to CTRL levels following the 7-day recovery period, suggesting its ability to physiologically respond to food consumption and to the normalization of bodyweight.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue is involved in the production and release of anti-inflammatory adiponectin and pro-inflammatory cytokines–like tumor necrosis factor α (TNF-α), C-reactive protein (CRP), interleukin 6 (IL-6), and leptin. Skeletal muscle cells through resistance training exercise can be made to produce different families of anti-inflammatory myokines that lead to increased levels of adiponectin and reduced secretion of pro-inflammatory TNF-α, IL-6, and leptin ( de Assis and Murawska-Cialowicz, 2023 ). Pro-inflammatory cytokines like leptin have been found to be associated with multiple different cancer developments, thereby establishing a link between cancer and obesity ( Moodi et al, 2021 ).…”
Section: Molecular Mechanisms Underlying the Benefits Of Exercise In ...mentioning
confidence: 99%
“…Besides, leptin can cause enhanced expression of angiogenic (vascular endothelial growth factor, VEGF), inflammatory factors (TNF-α, IL-6), and anti-apoptotic proteins by acting as a mitogen. Interestingly, resistance exercise exerts an anti-inflammatory effect by lowering leptin levels ( Divella et al, 2016 ; Nuri et al, 2016 ; de Assis and Murawska-Cialowicz, 2023 ). Studies on colon cancer and breast cancer have provided evidence to link leptin with neoplastic processes; however, limited information is available on this association in other types of cancer ( Nuri et al, 2016 ; Lin and Hsiao, 2021 ; de Assis and Murawska-Cialowicz, 2023 ).…”
Section: Molecular Mechanisms Underlying the Benefits Of Exercise In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Біологічна роль ключових адипокінів білої жирової тканини (лептину, адипонектину) в патогенезі ожиріння добре відома та описана в літературі [5,11,34]. Водночас роль адипокінів вісцерального жиру, зокрема вісфатину, є дискутабельною і становить науковий інтерес.…”
Section: результати обговоренняunclassified